Evaluating the environmental effects of open dumps and waste farming: A case study: Effects of Open Dumping - Ria Ghosh; Tumpa Hazra; Indranil Mukherjee; Ushcats, Svitlana; Md WasimAkram; Md Athar Akram; Mohd Sayeed Ul Hasan; Tinku Biswas; Sheela Malik; Md Anzar Rabbani; et al. (Ecological Questions, 2024)
Dhapa, the landfill situated in Kolkata, is a very active site for municipal dumping. A humongous amount of municipal solid waste is added in this dump daily and the nearby farmlands produce a significant yield for the local population. The current study seeks to examine the environmental associated with leachate migration due to open dumping of unsorted solid waste in Dhapa, Kolkata, India. Also, the second goal of the study is to assess the risk to public health associated with the consumption of agricultural products possibly contaminated with heavy metals through soil and groundwater. The seasonal soil and groundwater sample, and samples of products grown near the landfill were collected around the periphery of Dhapa. The presence of heavy metals in the samples was determined using classical methods in a specialized laboratory. The soil and groundwater results compared to FAO/WHO, and BIS/WHO was found that toxic metal Cd, Cr, Zn, Pb & Hg were present in high concentrations. For the vegetables grown at the site fields, multiple samples were collected as multiple different vegetables are grown around the year, it was found that mainly Cd, Cr, Zn, Pb and Hg exceeding Indian permissible standards of consumptions many fold. Finally by the use of multiple indices like Average Daily Dose (ADD) & Chronic Daily Intake (CDI) along with Hazard Quotient (HQ) it was found that carcinogenic risk, on human health, was highest in the ground water and vegetables. The current study fills the gap associated with the scientific substantiation of actively developing environmental hazards at the regional level.